The matrix of modernism : Pound, Eliot, and early twentieth-century thought - Schwartz, Sanford, 1948- (Princeton University Press, 1985)
Sanford Schwartz situates Modernist poetics in the intellectual ferment of the early twentieth century, which witnessed major developments in philosophy, science, and the arts. Beginning with the works of various philosophers--Bergson, James, Bradley, Nietzsche, and Husserl, among others--he establishes a matrix that brings together not only the principal characteristics of Modernist/New Critical poetics but also the affiliations between the Continental and the Anglo-American critical traditions. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Keywords: Pound, Ezra, -- 1885-1972 -- Criticism and interpretation.; Eliot, T. S. -- (Thomas Stearns), -- 1888-1965 -- Criticism and interpretation.; Eliot, T. S. -- (Thomas Stearns), -- 1888-1965; Pound, Ezra, -- 1885-1972; American poetry -- 20th century -- History and criticism.; Modernism (Literature) -- English-speaking countries.; English poetry -- 20th century -- History and criticism.; Philosophy, Modern -- 20th century.; Philosophy in literature.; Poésie américaine -- 20e siècle -- Histoire et critique.; Modernisme (Littérature) -- Anglophonie.; Poésie anglaise -- 20e siècle -- Histoire et critique.; Philosophie -- 20e siècle.; Philosophie dans la littérature.; HISTORY -- General.; LITERARY CRITICISM -- Poetry.; American poetry; English poetry; Modernism (Literature); Philosophy in literature; Philosophy, Modern; English-speaking countries; 1900-1999; Criticism, interpretation, etc.